(untitled) (Global Journals of Research in Engineering, 2012)
Water is described as a universal solvent which is the most abundant and useful compound that nature has provided Two main sources of water are surface and underground water Among the many essential elements for the existence of human beings animal and plants water is rated as one of the most important elements for human living Man can survive for weeks without food but a few days without water Sand has been used to purify water for over a thousand years and it still remains the dependable methods of making water fit for drinking The idea of water sand filtration can be seen when water taken from sandy river beds is generally pure because it has percolated through the sand grains where harmful bacteria are removed As a result of high demand for quality and clean water by the society various means to meet this demand have been constructed Though many of these means are not easily accessible by some communities due to unavailability high cost or complexity of usage This has led to the design and construction of water filters which can be accessible by all communities Data obtained from our laboratory results clearly shows that an appreciable degree of treatment had taken place when the designed filter was used in this paper we describes the fabrication rapid sand filteration equipment by using glass boxes sand Activated carbon mesh coagulant etc and also tested the raw water treated water byu using WHO standard analytical procedures